Meningkatkan Literasi Akademik Guru Melalui Pengenalan Artikel Jurnal Ilmiah - Saugadi Saugadi; Alfansyah Fathur; Andhy Saputra (TOLIS MENGABDI : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity themed "Introduction to Scientific Journal Articles" aimed to enhance teachers’ academic literacy through scientific writing training. Conducted online, the program involved approximately 50 subject teachers (MGMP) from Kotawaringin Timur Regency. The training covered article structure, academic writing conventions, and strategies for publishing in accredited journals. The results indicated that participants gained not only conceptual understanding but also practical skills in academic writing. Their high level of enthusiasm was reflected in active participation and expressed interest in beginning the publication process. This activity demonstrates the effectiveness of training-based approaches in fostering an academic culture among teachers and encouraging them to contribute actively to knowledge development through scientific publications.